Modulation of hypercapnic respiratory response by cholinergic transmission in the commissural nucleus of the solitary tract - Furuya, Werner I. [UNESP]; Bassi, Mirian [UNESP]; Menani, José V. [UNESP]; Colombari, Eduardo [UNESP]; Zoccal, Daniel B. [UNESP]; Colombari, Débora S. A. [UNESP] (Springer Nature, 2020)
The nucleus of the solitary tract (NTS) is an important area of the brainstem that receives and integrates afferent cardiorespiratory sensorial information, including those from arterial chemoreceptors and baroreceptors. It was described that acetylcholine (ACh) in the commissural subnucleus of the NTS (cNTS) promotes an increase in the phrenic nerve activity (PNA) and antagonism of nicotinic receptors in the same region reduces the magnitude of tachypneic response to peripheral chemoreceptor stimulation, suggesting a functional role of cholinergic transmission within the cNTS in the chemosensory control of respiratory activity. In the present study, we investigated whether cholinergic receptor antagonism in the cNTS modifies the sympathetic and respiratory reflex responses to hypercapnia. Using an arterially perfused in situ preparation of juvenile male Holtzman rats, we found that the nicotinic antagonist (mecamylamine, 5 mM), but not the muscarinic antagonist (atropine, 5 mM), into the cNTS attenuated the hypercapnia-induced increase of hypoglossal activity. Furthermore, mecamylamine in the cNTS potentiated the generation of late-expiratory (late-E) activity in abdominal nerve induced by hypercapnia. None of the cholinergic antagonists microinjected in the cNTS changed either the sympathetic or the phrenic nerve responses to hypercapnia. Our data provide evidence for the role of cholinergic transmission in the cNTS, acting on nicotinic receptors, modulating the hypoglossal and abdominal responses to hypercapnia.
Keywords: Acetylcholine; Brainstem; Chemoreflex; Hypercapnia; Muscarinic receptors; Nicotinic receptors